Determinants of bank profitability in developing economies: empirical evidence from the South Asian banking sectors - Sufian, Fadzlan (Taylor and Francis (Routledge), 2012)
This study seeks to examine the performance of 77 Bangladeshi, Sri Lankan, and Pakistani commercial banks between 1997 and 2008. The empirical findings suggest that bank specific characteristics – in particular, liquidity, non-interest income, credit risk, and capitalization – have positive and significant impacts on bank performance, while cost is negatively related to bank profitability. As for the impact of macroeconomic indicators, the results suggest that economic growth has positive and significant impact, while inflation has no significant impact on bank profitability. During the period under study, the empirical findings indicate that private investment is positively related to bank profitability, while private consumption expenditure exhibits negative impact. However, the impact is not uniform across the countries studied.